Soreness and ulcers 3: due to vesiculobullous disease 1 - Nikitakis, Nikolaos (Henry Stewart Talks, 2017)
Vesiculbullous diseases: definition and causes, Hereditary diseases, Allergy, Infections, Immunologically-mediated diseases, Diseases showing frequent subepithelial blister formation, Mucous membrane pemphigoid, Bullous pemphigoid, Dermatitis herpetiformis, Linear IgA disease, Epidermolysis bullosa acquisita, Angina bullosa hemorrhagica